Ninety days of solitary confinement: Prison experience of the 'pervodumtsy' (First Duma deputies) convicted of signing the Vyborg Appeal - D.M. Usmanova; S.V. Shebalkov (Ученые записки Казанского университета: Серия Гуманитарные науки, 2017)
The paper analyzes the little-researched problem of prison experience of the First Duma deputies (“pervodumtsy”) who were penalized in 1907 for signing the Vyborg Appeal. As the result of the action carried out by the former deputies in Vyborg (Grand Duchy of Finland), 167 people were sentenced to 3 months of imprisonment and deprivation of the political rights. Therefore, the “pervodumtsy” became political prisoners. The study reconstructs the peculiarities of deputies' prison confinement on an extensive basis of personal sources and also archival documentation from the Russian Federation State Archive. The location of prisons, where the former deputies were held, has been identified. The paper involves the prison memoirs of such prominent public and political figures as Vladimir Dmitrievich Nabokov, Victor Petrovich Obninsky, Vladimir Andreevich Obolensky, Nikolay Andreevich Borodin, Yakov Kondratyevich Imshenetsky, Sergey Dmitrievich Urusov, et al. The prehistory of the “Vyborg procedure” of 1907 has been considered. The social composition of convicted deputies has been noted. The study traces difficulties of the prison experience, analyzes various spheres of prisoners' everyday life in prisons. Particular attention in the paper has been paid to the question of the interaction between the political prisoners and the prison authorities. The study highlights the distinctiveness of the new convict group for the Russian empire and brings to light the influence of the prison experience on the deputies' subsequent life.